Delivery of Curcumin Using Zein-Gum Arabic-Tannic Acid Composite Particles: Fabrication, Characterization, and in vitro Release Properties - Zhang, Yiquan; Liu, Guiqiao; Ren, Fazheng; Liu, Ning; Tong, Yi; Li, Yi; Liu, Anni; Wu, Lida; Wang, Pengjie (Frontiers in Nutrition, 2022)
The application of curcumin (Cur) in fat-free food is limited due to its poor water solubility, stability and bioaccessibility. In this study, zein-gum arabic-tannic acid (zein-GA-TA) composite particles with high physical stability were fabricated to deliver Cur (ZGT-Cur). Their stability and in vitro release properties were also evaluated. The results showed that the thermal and photochemical stability of Cur was improved after loading into composite particles. Meanwhile, the retention rate of Cur in ZGT-Cur composite particles was enhanced compared with Z-Cur or ZG-Cur particles. Fourier transform infrared (FTIR) spectroscopy confirmed that the hydrogen bond within the particles was greatly enhanced after the addition of tannic acid (TA). The in vitro antioxidant activity of Cur in ZGT-Cur composite particles was higher in terms of 2,2'-azino-bis (ABTS) (93.64%) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) (50.41%) compared with Z-Cur or ZG-Cur particles. The bioaccessibility of Cur in ZGT-Cur composite particles was 8.97 times higher than that of free Cur. Therefore, the particles designed in this study will broaden the application of Cur in the food industry by improving its stability and bioaccessibility.